Integrity of Multiple Memory Systems in Individuals With Untreated Obstructive Sleep Apnea - Jackson, Melinda L.; Rayner, Genevieve; Wilson, Sarah; Schembri, Rachel; Sommers, Lucy; O’Donoghue, Fergal J.; Jackson, Graeme D.; Tailby, Chris (Frontiers in Neuroscience, 2020)
Many individuals with obstructive sleep apnea (OSA) experience working- and autobiographical-memory impairments, and high rates of depressive symptoms. This study aimed to examine (i) behavioral responses and (ii) neural activation patterns elicited by autobiographical and working memory tasks in moderate-severe untreated obstructive sleep apnea (OSA) patients and healthy controls, and (iii) whether variability in autobiographical and working memory activation are associated with task performance, OSA severity and depressive symptoms. Seventeen untreated OSA participants were comparable to 16 age-matched healthy controls with regards to both activation and behavioural performance. OSA was associated with worse mood symptoms and poorer personal semantic memory. Higher levels of nocturnal hypoxia were associated with increased activation in the occipital cortex and right cerebellum in OSA participants, however, no significant relationships between activation and task performance or depressive symptomatology were observed. The neurocognitive substrates supporting autobiographical recall of recent events and working memory in younger, recently-diagnosed, individuals with OSA appear to be indistinguishable from healthy age-matched individuals. These finding point to the importance of early diagnosis and treatment of OSA in order to preserve cognitive function.